Fósiles deformados y otras estructuras microtectónicas en la formación hiló (albiano) alrededores de sasaima, cundinamarca (colombia) (1984)
The Hiló Formation (middle to upper Albian) consists of dark bitominous sediments which include mainly calcareous shales, fine-grained sandstones and calcareous to arenaceous cherts. The rocks of the Hiló Formation contain many deformed elements that were affected by tectonic processes. Among these we note: elongated fossils (ammonites and bivalves), elongated pyrite nodules, microfolds, horizontal stylolites, folding striations and vertical sub-horizontal joints.The systematic measurement of the above-mentioned structural and microtectonic elements in an outcrop located in the vicinity of Sasaima (Cundinamarca) has made the determination of the paleostresses possible, which have affected the rocks of the Hiló Formation. The results obtained from the analysis of the structural parameters mentioned above made it possible to determine the direction of maximum elongation (o3) as 20lo±3°/26°± 8° and the direction of maximun compression (o1) as with an azimuth of 3200 (= l400E). These values define the stress system in the area of Sasaima.  A quick visit to another outcrop located to the SW of Sasaima, on the road that leads from Villeta to Guayabal de Síquima, near the village of Chimbe, confirms the conclusions deduced from the first outcrop.